Estimates of Genetic and Phenotypic Trends of Growth Traits in Bali Cattle - A Gunawan; R Sari; . Jakaria (Media Peternakan, 2012)
The aim of this study was to estimate genetic and phenotypic trends for growth traits including birth (BW), weaning (WW) and yearling weight (YW) in Bali cattle. The number of cattle used to determine growth traits of BW, WW, and YW were 235, 215, and 178 heads, respectively. Estimation of breeding value, phenotypic and genetic correlation were calculated by Restricted Maximum Likelihood and General Linier Model (GLM) procedures, respectively. Genetic trends analysis was performed using the regression mean breeding values on birth year. Phenotypic and genetic correlation among BW and WW were 0.10 and 0.08 respectively and 0.90 and 0.70 for WW and YW respectively. The phenotypic trends for traits of birth and weaning weight were constant, whereas yearling weight was fluctuating from 2000 to 2008. Likewise, in the case of genetic trends, the birth and weaning weight were constant from 2000 to 2008 except for WW in 2005, whereas the genetic trends for yearling weight showed a fluctuation of wide range. According to the breeding value estimated for all traits, the best was the sire No. 0565, whose breeding value for BW, WW and YW were +0.07, +2.79, and +10.25 kg, respectively higher than the mean value of the population. The genetic trends showed that there have been a significant and positive genetic improvement in all growth traits and indicate that selection would be effective. Genetic correlation between WW and YW was high (0.70) which indicates that the selection on weaning weight might also increase yearling weight in Bali cattle.